Williams Obstetrics - Cunningham, F. Gary; Bloom, Steven L.; Leveno, Kenneth J (McGraw-Hill, 2018)
This landmark text begins with fundamental discussions of reproductive anatomy and physiology. These dovetail into clinical chapters covering obstetrical complications such as preterm labor, pregnancy-related infection, hemorrhage, and hypertension, among others.